The six-shooter state: public and private violence in American politics - Obert, Jonathan (Cambridge University Press, 2018)
"American violence is schizophrenic. On the one hand, many Americans support the creation of a powerful bureaucracy of coercion made up of police and military forces in order to provide public security. At the same time, many of those citizens also demand the private right to protect their own families, home, and property. This book diagnoses this schizophrenia as a product of a distinctive institutional history, in which private forms of violence - vigilantes, private detectives, mercenary gunfighters - emerged in concert with the creation of new public and state forms of violence such as police departments or the National Guard. This dual public and private face of American violence resulted from the upending of a tradition of republican governance, in which public security had been indistinguishable from private effort, by the nineteenth century social transformations of the Civil War and the Market Revolution"--